Effects of sorafenib and cisplatin on preneoplastic foci of altered hepatocytes in fetal turkey liver. Issue 1 (8th November 2016) - Kaestner, Bettina; Spicher, Karsten; Jaehde, Ulrich; Enzmann, Harald
Abstract : Foci of altered hepatocytes (FAH) were induced in fetal turkey liver (FTL) by diethyl nitrosamine. Sorafenib but not cisplatin enhanced the development of FAH by increasing cell proliferation. This is indicative of a potential promotion effect of sorafenib on hepatocarcinogenesis. Abstract : Foci of altered hepatocytes (FAH) were induced in fetal turkey liver (FTL) by diethyl nitrosamine. FAH in FTL were resistant to iron overload similar to FAH in humans and rodents. The mitotic index was significantly higher in FAH (6.2 mitosis in 1000 hepatocytes) than in extrafocal liver tissue (1.8 mitosis in 1000 hepatocytes). The calculation of the net growth rate based on both cell proliferation (mitosis) and cell death (TUNEL positive) revealed a threefold growth advantage of the FAH over the surrounding liver. Two well established anti-tumor substances from different chemical classes, different modes of action and with different clinical use in the treatment of hepatocellular carcinoma (HCC) were used to study their effect on FAH. Sorafenib is the only approved drug for systemic pharmacological treatment of HCC; cisplatin has been used for many years in hepatic arterial infusion. Cisplatin had no clear effect on number of size of FAH, cell proliferation (mitosis) or cell loss (TUNEL positive). Sorafenib enhanced the development of FAH. Morphometric quantification revealed a sorafenib-induced 2–3-fold increase in number (FAH per cm 2 and FAH per cm 3 ), size and volume fraction of FAH. This unexpected finding was confirmed in two experiments. The effect was driven by an increased cell proliferation in the FAH, resulting in an increased, 5.4-fold growth advantage of FAH versus the surrounding liver in sorafenib-treated FTL. In this model, sorafenib has a promoting effect on preneoplastic FAH. This might be of relevance for the treatment of patients with long term survival perspective, e.g. in an adjuvant setting.